2018
DOI: 10.1128/genomea.00088-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Mn(II)-Oxidizing Pseudomonas resinovorans Strain MO-1

Abstract: Pseudomonas resinovorans strain MO-1, which possesses a high ability to oxidize Mn(II), has been isolated from oligotrophic pond sediment. The draft genome sequence consists of 6,252,942 bp and has a G+C content of 63.4%. Strain MO-1 has 5,694 coding sequences, including 13 putative Mn(II) oxidation genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The application of the P. resinovorans AF22 strain on rice plants resulted in a significant increase in shoot and root dry weight but did not increase shoot height or root length (Habibi et al 2019). Different P. resinovorans isolates might play additional roles in improving soil quality, as Matsushita et al (2018) have reported about the ability of the P. resinovorans MO-1 strain that can oxidize Mn (II) and produce Mn (III, IV) oxide minerals, which take part in different biological processes and functions, such as photosynthesis, or protection against UV radiation, ROS and predation (Geszvain et al 2012). The application of P. mendocina in vivo resulted in enhanced soil aggregate stability and significant improvement of the dehydrogenase and phosphatase activities by 21 and 89%, respectively (Kohler et al 2006).…”
Section: Enhancement Of Tomato Growthmentioning
confidence: 99%
“…The application of the P. resinovorans AF22 strain on rice plants resulted in a significant increase in shoot and root dry weight but did not increase shoot height or root length (Habibi et al 2019). Different P. resinovorans isolates might play additional roles in improving soil quality, as Matsushita et al (2018) have reported about the ability of the P. resinovorans MO-1 strain that can oxidize Mn (II) and produce Mn (III, IV) oxide minerals, which take part in different biological processes and functions, such as photosynthesis, or protection against UV radiation, ROS and predation (Geszvain et al 2012). The application of P. mendocina in vivo resulted in enhanced soil aggregate stability and significant improvement of the dehydrogenase and phosphatase activities by 21 and 89%, respectively (Kohler et al 2006).…”
Section: Enhancement Of Tomato Growthmentioning
confidence: 99%